ANALYSIS OF TIM BENDZKO'S SONG ''HOCH'' USING BARTES' SEMIOTIC METHOD - Van Delzen, June Noya; Loupatty, Jeyssen L; Noya Van Delzen, Zipora V.; Limba, Gysella V. (Pattimura Excellence Journal of Language and Culture, 2023)
This research aims to analyze the meanings of the song Hoch by Tim Bendzko. The method used is descriptive qualitative with Barthes' semiotic approach. The semiotic method is a scientific discipline and analysis method that can examine the signs contained in an object to know the meaning contained in the object. Semiotics is a science or method for studying signs in Barthes' terms. Semiology is a constraint to study how humanity (humanity) interprets things (things), interpret (to signify), in this case, cannot be confused with communicating (to communicate). The author analyzes several meanings in the song Hoch by Tim Bendzko: Denotation, Connotation and Myth. Denotation meaning is the actual meaning. This order describes the relationship between the signifier and the sign in the sign and between the sign and its referent in reality. The connotation meaning itself is a meaning that is more subjective and emotional than the denotation meaning. Mythical meaning is a representation built by the society of social and natural reality. Myths not only refer to stories from ancient times but also include modern representations that we find in mass media and popular culture. From this research, the author concludes that Lagu Hoch is a song that tells the story of a person's persistence to get a better life.